Penerapan Aplikasi 5G Untuk Mengevaluasi Layanan Penggunaan Aplikasi Gojek Menggunakan ITIL V3 Domain Service Design - Ikhtiarti, Dyah; Sari, Dewi Novita; Sutabri, Tata (Universitas Respati Indonesia, 2023)
In an era of sophistication, 5G technology is considered to be able to encourage the development of the service industry, one of which is the use of the online transportation ordering application (Gojek). The range of the network used will be further increased, so that the application will be more and more in demand. To find out the user's assessment of the system, it is necessary to analyze user services for the Gojek application using the ITIL V3 framework. Focusing on the design service domain which consists of sub domains namely design coordination, service catalog, service level management, availability management, service design process, capacity management, information security. The results of this study show that the average value of the subdomain is 3.65, with the largest current maturity value in the service catalog subdomain, which is 3.75. In the design coordination subdomain, there were 3.72, capacity management was 3.70, in the service level management subdomain was 3.60, information security was 3.64, availability management was 3.58, and service design process was 3.50. it can be concluded that all subdomains occupy maturity level 4, namely manage and measurable, which means that the Gojek application is running well. However, it still provides recommendations for system improvements in the future.